2015
DOI: 10.2147/sar.s78773
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and factors associated with regular khat chewing among university students in Ethiopia

Abstract: PurposeKhat (Catha edulis) is commonly chewed for its psychostimulant and euphorigenic effects in Africa and the Arabian Peninsula. Students use it to help them study for long hours especially during the period of examination. However, how regularly khat is chewed among university students and its associated factors are not well documented. In this article we report on the prevalence of and factors associated with regular khat chewing among university students in Ethiopia.MethodsWe did a cross-sectional study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
47
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 49 publications
4
47
4
Order By: Relevance
“…Similarly reports from Eastern part of Ethiopia documented a 25 % for life time khat use prevalence 34 . Other school, university, and community based studies conducted in Ethiopia also reported a much higher figure than the reports we found among Sidama students 32,34,38 . For instance the reported overall khat use prevalence among Agaro high school students was 64%.…”
Section: Discussioncontrasting
confidence: 78%
See 4 more Smart Citations
“…Similarly reports from Eastern part of Ethiopia documented a 25 % for life time khat use prevalence 34 . Other school, university, and community based studies conducted in Ethiopia also reported a much higher figure than the reports we found among Sidama students 32,34,38 . For instance the reported overall khat use prevalence among Agaro high school students was 64%.…”
Section: Discussioncontrasting
confidence: 78%
“…Compared to Ethiopian university based khat survey reports, the prevalence for students of Sidama seems to fall within the documented khat use prevalence range but lesser than the community based reports. For instance university based prevalence studies conducted in Ethiopia reported khat use prevalence ranging from 13.4% to 41% for lifetime, 7% to 20.3% for past 12 months, and 6.3% to 33.1% current or past 30 days 32 . Much bigger prevalence reports noticed in Ethiopia are from one school survey report and other community based surveys 7,34 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations